Comparison of the Effects of Weight Bearing and Non-weight Bearing Exercise on Pain, Range of Motion and Disability in patients with Total Hip Replacement - Tauqeer, Habiba; Gul, Hina; Mustafa, Rida; Javed, Syda Nimra (Pakistan Armed Forces Medical Journal, 2025)
Objective: To compare the effects of weight bearing and non-weight bearing exercise on pain, range of motion and disability in patients with total hip replacement.Study Design: Randomized clinical trialPlace and Duration of Study: Outpatient department of Physical Therapy, Winner Health Care Hospital Gujranwala /6 monthsMethodology: The study was conducted on 22 patients that undergo total hip replacement. All patients randomly allocated to weight bearing exercise group and non-weight bearing exercise group. Both groups received 12 treatment sessions for 6 weeks. Numeric Pain Rating Scale, Goniometer, hip disability and osteoarthritis outcome score were used to measure the treatment effect at baseline and after 6 weeks treatment of total 12 sessions in 6 weeks, with 2 sessions per week. The clinical trial number of this study is NCT05375565.     Results: This study showed that pretreatment p value of numeric pain rating scale was 0.401 and of post treatment session was 0.270 which showed that there was a significant decrease in pain level in both groups. Range of motion also improved after taking intervention in both groups. In both groups, total hip disability and osteoarthritis outcome score in weight bearing exercise group was 21.05% at pre level and was 56.42% at post level while in non-weight bearing exercise group total HOOS score was 22.68% at pre level and 39.78% at post level.Conclusion: Weight-bearing exercise had proved to be more effective in treating disability as compared to non-weight bearing exercise in patients undergoing ..